1998
DOI: 10.1161/01.res.82.12.1298
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Production in Vascular Smooth Muscle Contributes to Oxidative Stress and Impaired Relaxation in Atherosclerosis

Abstract: The endothelium is a source of reactive oxygen species in short-term models of hypercholesterolemia and atherosclerosis. We examined a chronic model of atherosclerosis for increased vascular production of superoxide (O2-.) and determined whether endothelial overexpression of superoxide dismutase (SOD) would improve endothelium-dependent relaxation. Superoxide generation was 3 times higher in isolated aortas from Watanabe heritable hyperlipidemic (WHHL) rabbits (2 to 4 years old) compared with aortas from New Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
468
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 556 publications
(482 citation statements)
references
References 26 publications
11
468
0
3
Order By: Relevance
“…21 Briefly, aorta sections were incubated in PBS for 30 minutes at 37 C and then encircled with the hydrophobic pen. DHE (5 mmol/L) was topically applied, followed by incubation at 37 C in the dark for 30 minutes.…”
Section: Ros Productionmentioning
confidence: 99%
“…21 Briefly, aorta sections were incubated in PBS for 30 minutes at 37 C and then encircled with the hydrophobic pen. DHE (5 mmol/L) was topically applied, followed by incubation at 37 C in the dark for 30 minutes.…”
Section: Ros Productionmentioning
confidence: 99%
“…Incubation was continued for an additional 30 minutes in the presence of 2 µM dihydroethidium (Carter et al 1994;Miller et al 1998) (DHE, Molecular Probes). After incubation, PAEC were washed, placed in phenol-red-free and serum-free M199, and imaged.…”
Section: Determination Of Intracellular O 2 -mentioning
confidence: 99%
“…PAEC were incubated for 30 minutes with 2 µmol/L dihydroethidium ( (Carter et al 1994;Miller et al 1998) DHE, Invitrogen) after 1 hour incubation with 60 µmol/L H 2 O 2 in M199 or M199 as a control. After incubation with DHE, PAEC were washed in phenol-red-free M199 and imaged with a Zeiss fluorescent microscopy utilizing a rhodamine filter cube.…”
Section: Determination Of Intracellular O 2 -mentioning
confidence: 99%
“…7,8 In angiotensin II (Ang II)-induced hypertension, Ang-II stimulates vascular NADPH oxidase to produce superoxide, which not only inactivates NO and impairs vasomotor function 9,10 but also contributes to atherogenesis by the activation of VCAM-1. 11 The elevated superoxide is present throughout the atherosclerotic vessel wall, 12 and a major source of superoxide is from the electron transport chain in mitochondrial respiration. 13 Two recent studies have indicated that there is also a substantial increase of vascular superoxide with reduced NO release in deoxycorticosterone acetate (DOCA)-salt hypertension, 14,15 a model well known for its suppressed plasma renin and angiotensin levels.…”
mentioning
confidence: 99%